2016
DOI: 10.1186/s12866-016-0831-3
|View full text |Cite
|
Sign up to set email alerts
|

Whole genome sequencing of Salmonella Typhimurium illuminates distinct outbreaks caused by an endemic multi-locus variable number tandem repeat analysis type in Australia, 2014

Abstract: BackgroundSalmonella Typhimurium (STM) is an important cause of foodborne outbreaks worldwide. Subtyping of STM remains critical to outbreak investigation, yet current techniques (e.g. multilocus variable number tandem repeat analysis, MLVA) may provide insufficient discrimination. Whole genome sequencing (WGS) offers potentially greater discriminatory power to support infectious disease surveillance.MethodsWe performed WGS on 62 STM isolates of a single, endemic MLVA type associated with two epidemiologically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 35 publications
0
32
0
Order By: Relevance
“…WP_000193682.1). While there is no strict definition of maximum SNP differences to define clonality or outbreak status, studies on Salmonella enterica serovar Typhimurium have suggested that outbreak isolates may differ by up to 4 SNPs, although miniclusters can be identified within a larger outbreak with Յ2 SNP differences (19). For S. Java, the CDC previously reported python-implicated outbreaks with isolates with 0 to 2 SNP differences; cases from other U.S. states that fell within the same cluster were not closely genetically related (up to 24 SNPs) (20).…”
Section: Resultsmentioning
confidence: 99%
“…WP_000193682.1). While there is no strict definition of maximum SNP differences to define clonality or outbreak status, studies on Salmonella enterica serovar Typhimurium have suggested that outbreak isolates may differ by up to 4 SNPs, although miniclusters can be identified within a larger outbreak with Յ2 SNP differences (19). For S. Java, the CDC previously reported python-implicated outbreaks with isolates with 0 to 2 SNP differences; cases from other U.S. states that fell within the same cluster were not closely genetically related (up to 24 SNPs) (20).…”
Section: Resultsmentioning
confidence: 99%
“…Serotypes (O and H antigens), pathotypes and sequence types [like multi-locus sequence typing (MLST) based on 7–8 housekeeping genes] can be inferred from WGS data [ 12 , 19 21 ]. Moreover, WGS allows discrimination up to the single nucleotide polymorphisms (SNPs) level for real-time or retrospective investigation of outbreaks of E. coli [ 22 25 ], Salmonella enterica [ 26 31 ] or Klebsiella spp. [ 32 35 ].…”
Section: Escherichia Coli and Other Enterobacteriaceaementioning
confidence: 99%
“…In recent years, the decrease of the cost combined with high speed have made this approach an opportunity for it becomes more utilized in large bacterial outbreak investigations, including the use in public health microbiology and diagnostic, such as identification, typing, resistance detection, and virulence gene detection (Didelot et al, 2012 ; Wilson, 2012 ; Kwong et al, 2015 ). Salmonella genotyping based on WGS is replacing traditional methods and has proven very effective in identifying the source of outbreaks (Allard et al, 2012 ; Hoffmann et al, 2016 ), improved trace-back studies (Octavia et al, 2015a ; Hoffmann et al, 2016 ), predicted antimicrobial resistance (Zankari et al, 2013 ; McDermott et al, 2016 ) and elucidating the evolution of some Salmonella sub-types (Okoro et al, 2012 ; Zankari et al, 2013 ; Dimovski et al, 2014 ; Leekitcharoenphon et al, 2014 , 2016 ; Deng et al, 2015 ; Kariuki and Onsare, 2015 ; Fu et al, 2016 ; Phillips et al, 2016 ). In addition, WGS also provides ways to analyze more specific differentiation of strains focusing in genome adaptation.…”
Section: Genotypic Methodsmentioning
confidence: 99%